Linguistic Lyricism and Postmodern Discourse in Contemporary Kazakh Prose: The Case of Roza Mukanova - Zharylgapov, Zh.; Amangeldina, M.; Tleubekova, B.; Nurakhmetova, Z.; Abikhanova, G.; Zhakulayev, A.; Khassenov, B. (Forum for Linguistic Studies, 2025)
This article examines the interplay between lyricism and the postmodern artistic paradigm in contemporary Kazakh prose through the lens of Roza Mukanova’s short story The Prisoner. The research applies an integrated methodological framework combining poetic-stylistic, psychoanalytic, and interpretive approaches. Lyricism is analyzed as a literary device that reveals the protagonist’s inner world through poetic imagery and emotional expression, while postmodern elements – such as stream of consciousness, intertextuality, reminiscence, and symbolism – are shown to deepen the narrative's structural and semantic complexity. The analysis highlights internal monologues, imagined dialogues, and unconscious distress as key mechanisms that embody the lyrical mode of the text. Furthermore, the interplay between the authorial voice and the character’s speech, along with metaphorical imagery and symbolic constructs, collectively shapes the multilayered meaning of the narrative. Special attention is devoted to the linguistic features of lyrical prose as manifested in The Prisoner, including the use of emotionally charged metaphors, evaluative epithets, and rhetorical syntactic structures. These linguistic tools serve as markers of the protagonist’s inner fragmentation and spiritual longing, while stylistic devices such as repetition, anaphora, antithesis, and asyndeton intensify the text’s lyrical tone. Through the symbolic deployment of objects like “mirror,” “window,” and “threshold,” the story constructs an archetypal image of psychological captivity and the desire for transcendence. The findings establish The Prisoner as a distinctive example of artistic synthesis between lyricism and postmodernism. Mukanova’s story demonstrates the convergence of lyrical-existential depth and postmodern formal experimentation in Kazakh prose.
Keywords: Prose; Lyrical Prose; Inner World; Psychological Space; Literary Process; Kazakh Prose; Contemporary Kazakh Literature